2018
DOI: 10.1088/1757-899x/381/1/012162
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Behaviors of Cu/Al Laminated Composites

Abstract: Abstract. In order to research the hot deformation behaviors of Cu/Al laminated composites, isothermal hot compression tests were conducted on a Gleeble-1500D thermo-mechanical simulator in the temperature range of 300 ~ 450°C and strain rate range of 0.01 ~ 1 s -1 . After hot compression, the cooperative deformation behaviors between Cu and Al were discussed. The effects of deformation temperature and strain rate on the deformation behaviors were described using an Arrhenius-type constitutive equation. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…So that the mechanism of dynamic softening starts at a certain strain, then flow stress exhibits a dropping tendency and reach stable conditions with an increase of strain as reported by Liu and Wang. 12 At higher deformation temperature 450°C, the isothermally activated process strongly controls the hot deformation process, atomic movement and dislocation slip become easy. Thus, at peak flow stress, the softening mechanism initiated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So that the mechanism of dynamic softening starts at a certain strain, then flow stress exhibits a dropping tendency and reach stable conditions with an increase of strain as reported by Liu and Wang. 12 At higher deformation temperature 450°C, the isothermally activated process strongly controls the hot deformation process, atomic movement and dislocation slip become easy. Thus, at peak flow stress, the softening mechanism initiated.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that at similar working conditions, with an increase of Cu content in composite the densification increased. Liu and Wang 12 investigated the influence of bonding interface depends upon strain rate as well as deformation temperature through hot deformation of Cu/Al laminated composites. They found that to attain interface coordination during deformation the hard copper layer should produce a higher tension on the adjacent soft aluminium layer to increase the dislocation slip resistance significantly.…”
Section: Introductionmentioning
confidence: 99%
“…With proper extension of blade inlet and by enlarging the blade inlet angle along with the optimal slots the new impeller design leads to significant improvement in the pump cavitation performance [9,10]. An optimum value for vane rake angle for obtaining superior cavitation performance was proposed [11]. Based on the genetic algorithm and CFD simulation improved design for blade thickness and leading-edge ellipse ratio was also proposed [12].…”
Section: Introductionmentioning
confidence: 99%